The Role of Teachers in the Learning Process of Vocational High School Students for Assisting Children with Special Needs - Goa, Lorentius; Ngarawula, Bonaventura; Rozikin, Zainur (International Journal of Psychosocial Rehabilitation, 2020)
The main problem in this research is the social reality of the role of vocational school teachers in the learning process for children with special needs. The general objective of this study was to determine the role of vocational high school (SMK) teachers in the learning process for students for assistance for children with special needs at the Bhakti Luhur Foundation. The approach taken by researchers is qualitative. This qualitative research method is often called the naturalistic research method because the research is carried out in a natural setting; it is also called the ethnographic method because initially this method was more widely used for research in the field of cultural anthropology; it is referred to as a qualitative method because the data collection and analysis are more qualitative. This research was conducted at the Bhakti Luhur Vocational School of Malang. In qualitative research, researchers became the main instruments of research. Data collection techniques in this study were observation, interviews, documentation, and combination/triangulation. Analysis of the researchers’ data used coding as an analysis process. According to Strauss and Corbin, there are three types or types of data analysis (coding) processes, namely open coding, axial coding, and selective coding. So that the theory built based on the data is not wrong, the three kinds of coding must be carried out simultaneously in research. To obtain the validity of qualitative research data, including degrees of trust and internal validity (credibility), external validity (transferability), reliability (dependability), and objectivity (confirmability). Test data credibility or trust in qualitative research results include, among others, extended observations, increased perseverance in research, triangulation, discussions with colleagues, negative case analysis, and member checks. The research found that: (1). Learning planning undertaken by the teacher is preparing a syllabus, lesson plan, teaching materials, and other learning tools. (2). The role of the teacher in the Bhakti Luhur Vocational High School in the learning process is to develop an interest, as a motivator, and as an evaluator. This study recommends further research on the lives of children with special needs.